Sorption of 2,4-Dichlorophenol onto Organobentonites: Influence of Organic Cation Structure and Bentonite Layer Charge - Mei Huang; Runliang Zhu (Adsorption Science & Technology, 2011)
The influence of both the molecular structure of the organic cation and the layer charge on the bentonite on the sorption characteristics of organobentonites has been examined. The organic cations cetyltrimethylammonium bromide (CTMA), tetramethylammonium bromide (TMA) and Crystal Violet (CV) were selected for producing two bentonites with different layer charges. The results obtained showed that the adsorption capacities of the three organic cations towards bentonite were in the order CTMA < CV > TMA. TMA-bentonite had the smallest basal spacing values but the largest surface area, but both CV-bentonite and CTM-bentonite had small surface areas. The sorption capacity of 2,4-dichlorophenol onto CTMA-bentonite increased with increasing bentonite layer charge, while the reverse was observed with TMA-bentonite. With CV-bentonite, the sample with the lower layer charge showed only a limited capacity towards the sorption of 2,4-dichlorophenol, and exhibited a much smaller sorption capacity relative to CTMA-bentonite and TMA-bentonite. The results obtained in the present study indicate that CTMA aggregates during sorption and that siloxane surfaces provide the major sorption sites on CTMA-bentonite and TMA-bentonite, respectively. In contrast, both the organic cation and siloxane groups contributed weakly to the sorption of 2,4-dichlorophenol on CV-bentonite.